Exploring the Drive Motor of Electric Vehicles: Structure, Temperature Rises, and Operational Control of Permanent Magnet Motors - Zhongxian Chen; Jiayin Liu (World Electric Vehicle Journal)
The drive motor is a critical component of electric vehicles. The design of its structure, along with the regulation of temperature rises and operational control, significantly impact the overall performance of electric vehicles, affecting aspects such as dynamic response, anti-interference capabilities, speed stability, and efficiency. This paper provides a review and comprehensive analysis of the Special Issue titled “Temperature Field, Electromagnetic Field, and Operation Control of Permanent Magnet Motor for Electric Vehicles”, and discusses the future development directions of permanent magnet motors in electric vehicles. The analysis reveals that the structural design is crucial for both the static and dynamic performance of permanent magnet motors. Additionally, it is imperative to identify an optimal trade-off among various performance parameters in these motors. The paper also verifies several future development directions for permanent magnet motors, including high-speed control, the use of advanced silicon steel sheets, power quality, battery charging efficiency, and energy feedback.